2021
DOI: 10.3390/molecules26020309
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes and the Maintenance of Hematopoietic Homeostasis: New Perspectives and Opportunities

Abstract: Hematopoietic stem cells (HSCs) regularly produce various blood cells throughout life via their self-renewal, proliferation, and differentiation abilities. Most HSCs remain quiescent in the bone marrow (BM) and respond in a timely manner to either physiological or pathological cues, but the underlying mechanisms remain to be further elucidated. In the past few years, accumulating evidence has highlighted an intermediate role of inflammasome activation in hematopoietic maintenance, post-hematopoietic transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 152 publications
(148 reference statements)
1
10
0
Order By: Relevance
“…These observations and the fact that ROS released from mitochondria in a complosome activation-dependent manner enhances the intracellular level of Nlrp3 inflammasomes supports the concept that the complosome–Nlrp3 inflammasome interaction promotes proliferation of HSPCs [ 94 ]. In accordance with this concept, a recent report suggested that glucose influx to the developing vertebrate embryo expands murine early CD41 + HSPCs in hematopoietic organs, and this effect depends on Nlrp3 inflammasome activation and IL-1β release [ 95 ].…”
Section: Introductionsupporting
confidence: 62%
“…These observations and the fact that ROS released from mitochondria in a complosome activation-dependent manner enhances the intracellular level of Nlrp3 inflammasomes supports the concept that the complosome–Nlrp3 inflammasome interaction promotes proliferation of HSPCs [ 94 ]. In accordance with this concept, a recent report suggested that glucose influx to the developing vertebrate embryo expands murine early CD41 + HSPCs in hematopoietic organs, and this effect depends on Nlrp3 inflammasome activation and IL-1β release [ 95 ].…”
Section: Introductionsupporting
confidence: 62%
“…They also regulate the immune homeostasis of the barrier epithelia (including the skin) [ 33 , 34 ]. In addition, they have also been suggested to regulate normal processes that do not relate directly to microorganisms, including the balance between erythroid and myeloid differentiation [ 35 ], normal hematopoiesis [ 36 ], hepatic metabolism [ 32 ], sterile inflammation such as that in pregnancy [ 37 ], and crosstalk with autophagy that regulates cellular integrity and prevent tumorigenesis [ 38 ]. However, similar to many other immune entities, inflammasomes can cause disease when they are dysregulated.…”
Section: The Inflammasome In Pathological Wound Healingmentioning
confidence: 99%
“…This irreversible growth arrest of the cell was accompanied by a senescence-associated secretory phenotype (SASP) that could induce secondary senescence of endothelial cells, with an associated infiltration of macrophages and neutrophils resulting in endothelial damage and lung tissue thrombosis (115). Given involvement of the inflammasome in paracrine senescence (116) and purinergic P2Y 14 receptor modulation of stress-induced hematopoietic progenitor cell senescence (117,118), purinergic pathways may present new pharmacological avenues for controlling senescence-mediated morbidities from SARS-CoV-2 infection.…”
Section: Sars-cov-2 Interactions With the Purinomementioning
confidence: 99%